A VIEW OF PRAGUE IN MRŠTÍK'S NOVEL SANTA LUCIA - Dvořáková, Helena (Bohemica Olomucensia, 2021)
The study analyses the 22nd chapter of the novel Santa Lucia written by Vilém Mrštík, which contains almost exclusively a description of Prague observed from the window by the main character Jordán. This description is very subjective and emotional. The analysis focuses on the relationship between an observing subject and an observed object. In the text three different forms of Prague are distinguished: Prague-place, Prague-object and Prague-person. The signs of multisensoriality, expressivity, impressionism and romantism are detected.
Keywords: description; multisensoriality; synesthesia; anthropomorphization; expressivity; impressionism; romantism